The UK Clinical Guidelines for Alcohol Treatment (2025): an overview for gastroenterologists - Ewan Forrest; Steven Masson (Frontline Gastroenterology, 2026)
In November 2025, the Department of Health and Social Care of the UK Government published the Clinical Guidelines for Alcohol Treatment with the aim to improve outcomes for people experiencing harmful alcohol use and alcohol dependence by supporting service planners, commissioners and providers to deliver high-quality care. The guidelines are comprehensive; however, their size means that identifying areas of particular relevance to gastroenterologists and hepatologists can be difficult. This article aims to highlight those aspects of the guidelines which may be of interest to those working in gastroenterology. This review highlights sections of the guideline related to physical health risks of alcohol, detection and assessment of liver disease, assessment of alcohol use disorder in acute hospitals, the management of alcohol withdrawal and Wernicke’s encephalopathy, the general treatment of alcohol-related liver disease, relapse prevention and driving advice. This review highlights the priorities for gastroenterologists described in these national guidelines.